India : Maternal and Reproductive Health at a Glance - El-Saharty, Sameh; Ohno, Naoko; Sarker, Intissar; Secci, Federica; Rajan, Vikram (World Bank, Washington, DC, 2015)
India is the third largest economy and has the second largest population in the world. It achieved millennium development goal (MDG) on poverty reduction; however, gender inequality still persists. Maternal mortality rate is 190 deaths per 100,000 live births, representing a 65 percent decline from 1990. Fertility fell to 2.5, while contraceptive prevalence rate increased to nearly 55 percent. Seventy-four percent of women sought antenatal care (ANC) from a qualified provider and 52 percent of births were attended by qualified providers. Wide gaps in contraceptive prevalence rate (CPR) and access to skilled-birth attendance remain by geography and wealth quintile. India will focus on preventing unwanted pregnancies especially among adolescents; improving demand-side strategies; strengthening access and quality in public and private sectors; improving antenatal, intranatal, and postnatal care; strengthening monitoring and evaluation (M and E) systems and reducing inequities; and improving nutrition.